The small GTPases FoRab5, FoRab7, and FoRab8 regulate vesicle transport to modulate vegetative development and pathogenicity in Fusarium oxysporum f. sp. conglutinans - Xiangyu Tan; Lin Chen; Ying Chen; Yuxin Li; Lihan Lu; Erfeng Li (Frontiers in Microbiology)
Rab GTPases play a crucial role in facilitating the transportation of vesicles during the process of fungal biogenesis. Currently, there is limited understanding regarding the specific biological functions of Rab small GTPase elements within Fusarium oxysporum. In this study, we examined the three proteins FoRab5, FoRab7, and FoRab8 of Foc, which exhibit homology to the Rab protein family found in Saccharomyces cerevisiae. In addition, we also employed a PEG-mediated homologous recombination approach to create deletion mutants and complementary strains for the FoRab5, FoRab7, and FoRab8 genes, thereby facilitating a comprehensive investigation into the functional roles of these genes. FoRab5 was localized on vesicles of various sizes within the cell. Compared to the wild-type strain, the growth rate of the mutant ΔFoRab5 strain decreased, the aerial hyphae decreased, the sporulation decreased, and the spore germination rate decreased. The sensitivity to cell membrane stress, cell wall stress, and endoplasmic reticulum stress increased, the activity of laccase and glucoamylase decreased significantly, and the pathogenicity to cabbage seedlings decreased. FoRab7 was localized on the vacuolar membrane. Compared to the wild type, the growth rate of the mutant ΔFoRab7 strain decreased, the bacteria produced a large amount of pigment deposition, the aerial hyphae decreased significantly, the hyphal branches increased, and the mutant almost lost the ability to produce spores. The sensitivity to osmotic stress, cell membrane stress, cell wall stress, metal ion stress, and endoplasmic reticulum stress was enhanced, and the vacuole was fragmented. Laccase and glucoamylase activities decreased in a significant manner. Moreover, there was a decrease in the pathogenicity of cabbage seedlings. FoRab8 was localized at the tip of the mycelium. Compared to the wild type, the growth rate of the mutant ΔFoRab8 strain decreased, the sporulation decreased, and the sensitivity of the mutant to osmotic stress and endoplasmic reticulum pressure increased. There was a significant decrease in the activity of laccase, glucoamylase, and cellulase. A reduction in the pathogenicity to cabbage seedlings occurred. In summary, these results indicate that members of the Rab family proteins FoRab5, FoRab7, and FoRab8 regulate a series of processes such as growth, sporulation, pathogenicity, and ectoenzyme secretion in Foc.